Finding Aedes aegypti in a natural breeding site in an urban zone, Sao Paulo, Southeastern Brazil - Tamara Nunes Lima-Camara; Paulo Roberto Urbinatti; Francisco Chiaravalloti-Neto (Universidade de São Paulo, 2016)
ABSTRACT This is the description of how nine Aedes aegypti larvae were found in a natural breeding site in the Pinheiros neighborhood, city of Sao Paulo, SP, Southeastern Brazil. The record was conducted in December 2014, during an entomological surveillance program of dengue virus vectors, with an active search of potential breeding sites, either artificial or natural. Finding Ae. aegypti larvae in a tree hole shows this species' ability to use both artificial and natural environments as breeding sites and habitats, which points towards the importance of maintaining continuous surveillance on this mosquito in all kinds of water-holding containers.